The balloon-expandable Edwards Sapien 3 valve is superior to the self-expanding Medtronic CoreValve in patients with severe aortic stenosis undergoing transfemoral aortic valve implantation. Issue 6 (June 2017) - Gonska, Birgid; Seeger, Julia; Baarts, Justus; Rodewald, Christoph; Scharnbeck, Dominik; Rottbauer, Wolfgang; Wöhrle, Jochen
Abstract: Background: Residual paravalvular moderate or severe aortic regurgitation (AR) has been an independent risk factor for mortality after transcatheter aortic valve implantation (TAVI). The design of the third generation Edwards Sapien 3 (ES3; Edwards Lifesciences, Irvine, CA, USA) valve was optimized with an outer skirt to address the issue of paravalvular AR. Methods and results: We compared 100 consecutive patients treated with the ES3 for severe aortic stenosis with 100 patients treated with the Medtronic CoreValve (CV; Medtronic, Minneapolis, MN, USA) (Clinical Trial Registration:NCT02162069 ). We evaluated post-procedural AR, rate of permanent pacemaker implantation, device success, and 30-day clinical outcome according to the criteria of the Second Valve Academic Research Consortium (VARC-2). Frequency of post-procedural moderate or severe AR was significantly lower with ES3 compared to CV (0% vs. 20%, p  < 0.01), none or trace AR significantly higher with ES3 (69% vs. 38%, p  < 0.01) as well as device success (97% vs. 73%, p  < 0.01). There was a significantly lower need for permanent pacemaker implantation with ES3 compared with CV (14% vs. 31%, p  < 0.01). Cardiovascular mortality at 30 days was significantly lower with ES3 (0% vs. 6%, p  = 0.01), and the combined endpoint "early safety" was met significantly less with ES3 (10% vs. 21% with CV, p  = 0.03). Conclusions: Transfemoral TAVI with the ES3 compared with the CV was associated with a significantly lower rate of moderate or severe AR, significantly lower need for pacemaker implantation, and a significantly higher rate of device success according to VARC-2.